Increasing the revenue from lignocellulosic biomass: Maximizing feedstock utilization - Alonso, David Martin (Sci Adv, 2017)
The production of renewable chemicals and biofuels must be cost- and performance- competitive with petroleum-derived equivalents to be widely accepted by markets and society. We propose a biomass conversion strategy that maximizes the conversion of lignocellulosic biomass (up to 80% of the biomass to useful products) into high-value products that can be commercialized, providing the opportunity for successful translation to an economically viable commercial process. Our fractionation method preserves the value of all three primary components: (i) cellulose, which is converted into dissolving pulp for fibers and chemicals production; (ii) hemicellulose, which is converted into furfural (a building block chemical); and (iii) lignin, which is converted into carbon products (carbon foam, fibers, or battery anodes), together producing revenues of more than $500 per dry metric ton of biomass. Once de-risked, our technology can be extended to produce other renewable chemicals and biofuels.